Evaluating Postoperative Narcotic Use in Prepectoral Versus Dual-plane Breast Reconstruction Following Mastectomy. Issue 2 (February 2019) - Copeland-Halperin, Libby R.; Yemc, Louisa; Emery, Erica; Collins, Devon; Liu, Chang; Mesbahi, Ali N.; Venturi, Mark L.
Abstract : Background: The majority of postmastectomy breast reconstruction performed in the United States is device-based. Typically, a tissue expander or implant is placed in the dual-plane (ie, subpectoral). Prepectoral breast reconstruction with acellular dermal matrices following mastectomy is a relatively new technique that has favorable outcomes with minimal complications and satisfactory aesthetic results. Few studies have compared opioid use between the 2 approaches. This study compares duration of postoperative opioid use among patients undergoing prepectoral device-based breast reconstruction with those in whom dual-plane devices were placed. Methods: We reviewed the records of adult female patients aged 18 years or older who underwent prepectoral or dual-plane device-based breast reconstructions following mastectomy by one of the 2 plastic surgeons (A.M. or M.V.) from 2015 to 2017 at a large tertiary care hospital. Patients with a history of substance abuse, chronic pain, or who were already receiving opioid medication were excluded. Electronic medical records were reviewed and patient surveys were conducted during postoperative visits to determine postoperative opioid requirements. Results: During the study period, 58 patients underwent dual-plane breast reconstruction and 94 underwent prepectoral reconstruction. Demographics and comorbidities of the groups were similar. By multivariate regression analysis, the prepectoral reconstruction group required 33% fewer days on opioid analgesic medication ( P = 0.016) and were 66% less likely to require opioid prescription refills ( P = 0.027). There were no statistically significant differences in other outcomes or complications. Conclusion: Patients undergoing prepectoral tissue expander or implant-based reconstruction required fewer days of opioid pain medication than those managed with the dual-plane technique.